Correlation between the knowledge of structure and the writing ability of students in the Architecture department - Akhmad Sidiq (Universitas Merdeka Malang, 2023)
Students writing skill is usually influenced by knowledge of grammar. To improve their writing skills they need to master English structure because it is needed to improve students' writing skills.Writing without correct structure is difficult to understand and even meaningless. Moreover, the students should have knowledge of structure first before they conduct writing activities. This study is conducted to find out whether there is significant correlation between knowledge of structure and ability to write English sentences of studentsÂ Architecture Department at International Multimedia Engineering School. To solve this problem, this study was conducted in a correlation design. The result of this study found that the students who have knowledge of structure have good ability in writing. Therefore, the students are expected to have certain ways to learn English language skills especially about English structure and writing. The students are expected to read more English books so that students will be able to improve their English skills, especially for structure and writing.Â